The Available Waste-to-energy Potential from Agricultural Wastes in the Department of Córdoba, Colombia - Sagastume, Alexis; Mendoza, Jorge M.; Cabello, Juan J.; Rhenals, Jesús D. (International Journal of Energy Economics and Policy, 2021)
There is a large potential for biomass-based renewable energy production Colombia which mostly remains untapped, accounting for a marginal 0.8% of the electricity production. Moreover, Córdoba is a department with important developments in agriculture and agroindustry, where significant amounts of biomass wastes are generated. In total, these wastes have a yearly energy potential of 548 for the use of anaerobic digestion, and 1,159 GWh per year using direct combustion. These energy potentials can yield 126 GWh/year of electricity using anaerobic digestion, or 260 GWh/year using direct combustion (i.e. 9 to 18% of the current electricity demand). However, power generation systems based on direct combustion for biomass wastes are economically feasible only for the lower investment costs available in the market, while anaerobic digestion is feasible for the low and average investment costs available in the market. Moreover, the biogas potential is equivalent to 1.4 times the energy demand required to replace firewood for cooking in 32% of the department homes that use firewood. More investigation is needed to more accurately define the potentialities of biomass wastes for energy applications in the department, for more effective promotion of its implementation. Keywords: Renewable energy; biomass waste; waste-to-energy technologies; bioelectricity JEL Classifications: O, Q DOI: https://doi.org/10.32479/ijeep.10705